Causal association between peripheral immune cells and IgA nephropathy: a Mendelian randomization study - Li-Mei Liang; Li-Mei Liang; Liang Xiong; Liang Xiong; Xin-Liang He; Xin-Liang He; Lin-Jie Song; Lin-Jie Song; Xiaorong Wang; Xiaorong Wang; Yu-Zhi Lu; Hong Ye; et al. (Frontiers in Immunology, 2024)
BackgroundThe relationship between peripheral immune cells and immunoglobulin A nephropathy (IgAN) is widely known; however, causal evidence of this link is lacking. Here, we aimed to determine the causal effect of peripheral immune cells, specifically total white blood cells, lymphocytes, monocytes, basophils, eosinophils, and neutrophils, as well as lymphocyte subset traits, on the IgAN risk using a Mendelian randomization (MR) analysis.MethodsThe inverse-variance weighted (IVW) method was used for the primary analysis. We applied three complementary methods, including the weighted median, MR-Egger regression, and MR-PRESSO, to detect and correct for the effect of horizontal pleiotropy. Additionally, we performed a multivariable MR (MVMR) analysis, adjusting for the effects of C-reactive protein (CRP) levels. The roles of specific lymphocyte subtypes and their significance have garnered interest. Bidirectional two-sample MR analysis was performed to test the potential causal relationships between immune traits, including median fluorescence intensities (MFIs) and the relative cell count (AC), and IgAN.ResultsThe IVW-MR analysis suggested a potential causal relationship between lymphocyte counts and IgAN in Europe (OR per 1-SD increase: 1.43, 95% CI: 1.08–1.88, P = 0.0123). The risk effect of lymphocytes remained even after adjusting for CRP levels using the MVMR method (OR per 1-SD increase: 1.44, 95% CI: 1.05–1.96, P = 0.0210). The other sensitivity analyses showed a consistent trend. The largest GWAS published to date was used for peripheral blood immunophenotyping to explore the potential causal relationship between peripheral immune cell subsets and IgAN. Six AC–IgAN and 14 MFI–IgAN pairs that reached statistical significance (P < 0.05) were detected. Notably, CD3, expressed in eight subsets of T cells, consistently showed a positive correlation with IgAN. The bidirectional MR analysis did not reveal any evidence of reverse causality. According to the sensitivity analysis, horizontal pleiotropy was unlikely to distort the causal estimates.ConclusionsGenetically determined high lymphocyte counts were associated with IgAN, supporting that high lymphocyte counts is causal risk factor for IgAN.